Pengaruh Jumlah Zakat Produktif, Modal Awal Dan Lama Usaha Terhadap Tingkat Pendapatan Mustahik Di Baznas Provinsi Riau (Studi Kasus Kota Pekanbaru) - Ulfa, Surya; Misdawita, Misdawita -; Setiawan, Deny - (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study is to analyze whether the amount of productive zakat, intial capital and simultaneous effect on mustahik income at BAZNAS Riau Province. The data used in this research is secondary data obtained from agencies such az BAZNAS Riau Province and also quetionnaires. The data analysis method use multiple linear regression analysis and classical assumption test to see the influence between the independent variables and the dependent variable and is calculated using the E-views 9 application software with a population of 61 mustahik. The results of the analysis show that the amount of productive zakat,initial capital and length of business have a significant effect on mustahik income at BAZNAS Riau Province.